Evaluación de cinco láminas de riego en el cultivo de cannabis (cannabis sp.) bajo invernadero en el Campus Salache – UTC, cantón Latacunga, provincia de Cotopaxi, 2022-2023. - Gutiérrez Caiza, Nathaly Lizbeth (2023)
Hemp (Cannabis sp) is a plant with many lights and shadows that helps to restore soils contaminated with heavy metals. It has been proven that this plant has the property of absorbing and accumulating nickel, lead, cadmium, zinc, copper and chromium. in their tissues, especially in their leaves. The main objective of this research work is to evaluate the application of five irrigation sheets in the cultivation of cannabis (Cannabis sp.) under a greenhouse on the Salache - UTC campus, Latacunga canton, Cotopaxi province, 2022-2023. The treatments consisted of applying a lamina with 100% crop evapotranspiration (control), a 110% excess lamina and three deficient laminas 90%, 80% and 70% of crop evapotranspiration (Etc), under localized high-frequency irrigation. in the cultivation of Cannabis sp. The experimental design was completely randomized blocks with 5 repetitions under greenhouse conditions. The results allowed to identify the phenological phases and vegetative development. The Cannabis sp crop during its vegetative development was affected by whitefly and nitrogen deficiency. The analysis of variance and Tukey's test at 5% determined that there are no significant differences in the growth and diameter of the stem at 30, 60 and 92 days of the crop. That is, the applications of the five sheets do not influence the vegetative development of the Cannabis sp crop up to 92 days. A substrate for the development of Cannabis sp is recommended in a mixture of coconut fiber: 25%, blonde peat: 45%, perlite: 10%, earthworm humus: 10% and biocompost: 10%.